2020
DOI: 10.1063/5.0011044
|View full text |Cite
|
Sign up to set email alerts
|

Validated two-dimensional modeling of short carbon arcs: Anode and cathode spots

Abstract: In order to study the properties of short carbon arcs, a self-consistent model was implemented into a CFD code ANSYS-CFX. The model treats the transport of heat and electric current in the plasma and electrodes in a coupled manner and accounts for gas convection in the chamber. Multiple surface processes at the electrodes are modeled, including the formation of space-charge limited sheaths, ablation and deposition of carbon, and emission and absorption of radiation and electrons. The simulations show that the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 49 publications
2
29
3
Order By: Relevance
“…The lower is the distance between the electrodes, the higher is the ablation rate. Numerical simulations of carbon arc discharges at similar conditions 24 showed that the near-anode layer in plasma is quite narrow, considerably smaller than 0.5 mm. Therefore, if the gap width is kept above 0.5 mm, its variation should affect neither plasma parameters in the vicinity of the anode nor the heat flux from the plasma to the anode which can be determined as t 8\\ • w. The solutions plotted in Fig.…”
Section: Figure 9 Ablation Rate As a Function Of The Electrode Separa...mentioning
confidence: 98%
See 4 more Smart Citations
“…The lower is the distance between the electrodes, the higher is the ablation rate. Numerical simulations of carbon arc discharges at similar conditions 24 showed that the near-anode layer in plasma is quite narrow, considerably smaller than 0.5 mm. Therefore, if the gap width is kept above 0.5 mm, its variation should affect neither plasma parameters in the vicinity of the anode nor the heat flux from the plasma to the anode which can be determined as t 8\\ • w. The solutions plotted in Fig.…”
Section: Figure 9 Ablation Rate As a Function Of The Electrode Separa...mentioning
confidence: 98%
“…If there is a background gas, it will impede the flow of the ablated material away from the ablating surface 9,23 leading to its accumulation near the surface. This will create a returning flux of the ablated material back to the evaporation surface reducing the net ablation flux 24,25 :…”
Section: Iia Ablation In the Presence Of A Background Gasmentioning
confidence: 99%
See 3 more Smart Citations